2015
DOI: 10.1111/jsr.12330
|View full text |Cite
|
Sign up to set email alerts
|

NREM‐related parasomnias in Machado–Joseph disease: clinical and polysomnographic evaluation

Abstract: SUMMARYSpinocerebellar ataxias (SCA) are autosomal dominant neurodegenerative disorders that affect the cerebellum and its connections, and have a marked clinical and genetic variability. Machado-Joseph disease (MJD) or spinocerebellar ataxia type 3 (SCA3)-MJD/SCA3-is the most common SCA worldwide. MJD/SCA3 is characterized classically by progressive ataxia and variable other motor and non-motor symptoms. Sleep disorders are common, and include rapid eye movement (REM) sleep behaviour disorder (RBD), restless … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 33 publications
2
28
0
1
Order By: Relevance
“…They had reported significantly higher frequency of arousals from slow wave sleep to higher parasomnia complaints like confusional arousal/sleep terrors, higher REM sleep without atonia and more periodic limb movements of sleep. They showed that NREM parasomnias are significantly present in SCA3 [16]. However, our study was conducted only to study the SSD, hence Parasomnias could not be evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They had reported significantly higher frequency of arousals from slow wave sleep to higher parasomnia complaints like confusional arousal/sleep terrors, higher REM sleep without atonia and more periodic limb movements of sleep. They showed that NREM parasomnias are significantly present in SCA3 [16]. However, our study was conducted only to study the SSD, hence Parasomnias could not be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Various symptoms of SCA types 2 and 3 like gait, limb and truncal ataxia, frequent falls, dysarthria, saccadic disturbances and executive dysfunction attribute to the involvement of re-entrant circuits, which need thalamic integrity [9]. Silva et al [16] evaluated 47 genetically proven cases of SCA 3 by polysomnographic studies and compared the results of these studies with those of the controls. They had reported significantly higher frequency of arousals from slow wave sleep to higher parasomnia complaints like confusional arousal/sleep terrors, higher REM sleep without atonia and more periodic limb movements of sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Vice versa, patients suffering from primary malfunctions of the cerebellum can show a variety of sleep disorders (for a detailed review, see [11,[69][70][71][72][73]). For example, patients with spinocerebellar ataxias [69,70,74,75], which are characterized by degeneration of the cerebellum and its afferent and efferent connections, can show increased daytime somnolence as well as NREM-and REM-related parasomnias. These data underline that the cerebellum fine-tunes neocortical forms of sleeprelated activity.…”
Section: Sleep Disorders Can Lead To Cerebellar Malfunction and Vice mentioning
confidence: 99%
“…Other SCA3 series showed a reduction in REM sleep percentage and an increase in REM sleep latency and REM sleep arousals even in the absence of RBD (Boesch, Frauscher, Brandauer, Wenning, Högl, et al., ; Pedroso, Braga‐Neto, et al., ; Pedroso, França, et al., ; Raggi et al., ). SCA3 patients also have non‐rapid eye movement (NREM)‐related parassonias (Silva et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with RBD also experience pathological changes in basal ganglia anatomy, with neuroimaging studies showing reduced striatal dopaminergic activity (Pedroso et al., ). However, sleep disorders in neurodegenerative diseases may be associated with more diffuse structural damage in the central nervous system, more specifically to sleep–wake‐generating cells and their networking (Raggi et al., ; Silva et al., ).…”
Section: Discussionmentioning
confidence: 99%